Cyanide Anions as Nucleophilic Catalysts in Organic Synthesis - Kieslich, David; Christoffers, Jens (Synthesis, 2021)
The nucleophilic addition of a cyanide anion to a carbonyl group is the basis for several cyanide-catalyzed organic reactions, which are summarized in this review. Since cyanide is also a good leaving group, it is an excellent catalyst for transacylation reactions. As an electron-withdrawing group, it also stabilizes a negative charge in its α-position, thus allowing the umpolung of aldehydes to formyl anion equivalents. The two leading examples are the benzoin condensation and the Michael–Stetter reaction furnishing α-hydroxy ketones and 1,4-dicarbonyl compounds, which are both catalyzed by cyanides. The review also covers variants like the silyl-benzoin coupling, the aldimine coupling and the imino-Stetter reaction. Moreover, some cyanide-catalyzed heterocyclic syntheses are reviewed.1 Introduction2 Nucleophilic Additions2.1 Cyanohydrin Formation2.2 Corey–Gilman–Ganem and Related Oxidation Reactions2.3 Conjugate Addition2.4 Intramolecular Carbocyanation3 Transacylation Reactions3.1 Ester Hydrolysis and Transesterification3.2 Formation of Amides3.3 Ketones from Esters3.4 Esters from Ketones4 Transformations Involving an Umpolung4.1 Benzoin Condensation4.2 Aldimine Coupling4.3 Michael–Stetter Reaction4.4 Imino-Stetter Reaction5 Formation of Heterocycles5.1 Oxazolines from Isocyanoacetates5.2 Imidazoles from TosMIC via Oxazolines5.3 Bargellini Reaction6 Conclusion
Keywords: catalysis; cyanide; umpolung; benzoin condensation; Stetter reaction; heterocycles